Determination of sperm quality in decapod crustaceans - Harlioglu, Muzaffer Mustafa; Farhadi, Ardavan; Gur, Seyfettin (Elsevier, 2018)
The determination and control of sperm quality is an important concern for the crustacean aquaculture industry, both in production of well-established profitable species and in presenting novel species with elevated commercial interest. The determination of foresight predictors or indicators of sperm quality of decapods will be a priority in other areas of investigation and in the development of biotechnology companies. Sperm quality of decapod crustaceans is determined by analyzing different parameters (e.g., sperm number in vas deferens and spermatophore, sperm viability, acrosome reaction, spermatophore size, melanization and spermatophore absence rate and energy content of spermatophore). The present review identifies the most important factors affecting sperm production and quality in decapod crustaceans such as broodstock nutrition, water pollution, water temperature, captivity, eyestalk ablation, hormones, neurotransmitters, moulting, stress, disease, male age and size. It is hoped that this review will be particularly useful for researchers investigating methods to determine sperm quality of decapods and for crustacean farmers culturing decapods.
Keywords: Sperm concentration; Shrimp; Crab; Crayfish; Lobster